Effect of handoff on flow marking in a Diffserv Edge Router / by Omer Mahmoud Mohamed - Mohamed, Omer Mahmoud (International Islamic University Malaysia, 2002)
Differentiated Services have been proposed as scalable solution that can satisfy real time traffic. In a diffserv domain an Edge Router perfonns Multi Field classification and maintain per now profile. If a mobile node connects to a Diflserv domain, it is subjected to the same policing and shaping as done for the static nodes. When a mobile node moves and changes its connectivity from one RER to another, the new R ER does not have the context unless it is transferred from the old RER. A study is conducted considering a diffserv domain where RERs run three different marking schemes (TSW, srTCM, trTCM) to meler the flows and mark the packets. This thesis present~ the results of this study. which show that by transferring context during handoff leads to improvement in marking the now especially for TSW where the marking of packets reach stability qu1ckly and result in less delay and jitter. If the context is not transferred. lhen the marking at the new RER takes a while to reach stability. The instabi lity period is proportional to the window size setting. The results also show that the instabi lity caused by the hand ofT negatively effect the flows of the same class at the new RER.